INFORMATION SEEKING BEHAVIOUR OF PRIVATE SCHOOL STUDENT IN KENYA - Kwanya, Tom; Nyariki, Phylis (Edulib, 2019)
Information seeking behaviour is the collection of actions which people take to identify, seek, evaluate, select and use information to satisfy their information needs. People seek information to enable them to deal with a current need or build their knowledge base. Private school students in Kenya have unique demographic and psychographic attributes defined by their age and geographical contexts. These attributes influence their information needs as well as information seeking behaviour. This study analysed the demographic and psychographic attributes of private school students in Kenya as well as investigated the students’ information needs and information seeking behaviour. The study was conducted as a descriptive survey. Data was collected from 103 students using self-administered questionnaires hosted on Google Forms. The findings indicate that the majority of the students used the library at least once a month. Similarly, most of the students used the library to support their class work. The Internet was the most important source of information from which the majority of the students began their information search. Most of the students were disappointed, frustrated or confused while using the library. Nonetheless, they often got the information they need and perceived the library as useful.